2021
DOI: 10.1038/s41598-021-95758-1
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric real world evidence with palbociclib in hormone positive HER2 negative metastatic breast cancer in Indian population

Abstract: The combination of cyclin dependent kinase 4/6 inhibitors with endocrine therapy is the standard therapy in hormone receptor positive HER-2 negative metastatic breast cancer (HR+/HER2− MBC). Several randomized trials have shown the benefits of this combination, however, real world evidence in the Indian patients is warranted. The present study reports the largest real world multicentric data from Indian population on the use of Palbociclib in HR+/HER2− MBC. A multicentric study on the HR+/HER2− MBC patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Median PFS was 26.1 months (95% CI: 23.4–30.8) in patients receiving CDK4/6i treatment as a first-line therapy, while median PFS was 11.9 months (95% CI: 9.9–13.9) in patients receiving CDK/4/6i as subsequent lines of therapy ( Supplemental Figure 2 ). These data are consistent with results of phase III clinical trials 1 3 , 5 8 , 12 and with data from previously published real-world cohorts 24 27 of patients treated with ET plus CDK4/6i.…”
Section: Resultssupporting
confidence: 90%
“…Median PFS was 26.1 months (95% CI: 23.4–30.8) in patients receiving CDK4/6i treatment as a first-line therapy, while median PFS was 11.9 months (95% CI: 9.9–13.9) in patients receiving CDK/4/6i as subsequent lines of therapy ( Supplemental Figure 2 ). These data are consistent with results of phase III clinical trials 1 3 , 5 8 , 12 and with data from previously published real-world cohorts 24 27 of patients treated with ET plus CDK4/6i.…”
Section: Resultssupporting
confidence: 90%
“…Since the approval of palbociclib in February 2015 [ 3 ], CDK4/6 inhibitors have become a recommended treatment option for women of all ages with HR+/HER2– MBC [ 2 ], and the rapid adoption of this class of agents has facilitated collection of real-world data documenting patient experiences. Recent real-world data analyses have shown that palbociclib is effective in patients with HR+/HER2– MBC in routine US clinical practice, but detailed information about the use of CDK4/6 inhibitors specifically in older patients is limited [ [8] , [9] , [10] , [11] , [12] ]. The available real-world studies including older European patients (≥70 or ≥75 years) support the effectiveness or tolerability of palbociclib in these age groups [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, there is an accumulating body of real‐world evidence studies that have evaluated palbociclib in combination with an AI in patients with HR+/HER2− mBC in the 1L 16‐18,20,27‐29,31,47‐52 . The results here add to the understanding and support of the benefit of palbociclib plus an AI in the 1L for people with HR+/HER2− mBC in the real world setting.…”
Section: Discussionmentioning
confidence: 61%
“…To our knowledge, the P-REALITY X study is the In conclusion, there is an accumulating body of real-world evidence studies that have evaluated palbociclib in combination with an AI in patients with HR+/HER2À mBC in the 1L. [16][17][18]20,[27][28][29]31,[47][48][49][50][51][52] The results here add to the understanding and support of the benefit of palbociclib plus an AI in the 1L for people with HR+/HER2À mBC in the real world setting. In addition to significantly prolonged OS and rwPFS, treatment with palbociclib plus an AI in a heterogeneous population of men and postmenopausal women with HR+/HER2À mBC was associated with a longer TTC.…”
Section: Probability (%)mentioning
confidence: 59%